12.3k views
4 votes
Subtract (4x^2+8x-2) - (2x^2-4x+3)

Subtract (4x^2+8x-2) - (2x^2-4x+3)-example-1

2 Answers

5 votes

Answer:

=2x^{2} +12x-5[/tex]

Explanation:


=4x^(2) +8x-2-2x^(2)+4x -3\\=4x^(2)- 2x^(2) +8x+4x-2-3\\=2x^(2) +12x-5

User Yannick Pezeu
by
6.2k points
3 votes

Answer: 2x^2+12x-5

Explanation:

since you are subtracting, you can multiply the second equation by -1 and just add instead; so you would use the equation:

(4x^2+8x-2)+(-2x^2+4x-3) instead

User Kyle James Walker
by
5.7k points